2017
DOI: 10.1016/j.electacta.2017.04.158
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Ion Diffusion in Charged Nanopores with Anchored Terminal Groups

Abstract: We present coarse-grained simulation results for enhanced ion diffusion in a charged nanopore grafted with ionomer sidechains. The pore surface is hydrophobic and its diameter is varied from 2.0 nm to 3.7 nm. The sidechains have from 2 to 16 monomers (united atom units) and contain sulfonate terminal groups. Our simulation results indicate a strong dependence of the ion diffusion along the pore axis on the pore parameters. In the case of short sidechains and large pores the ions mostly occupy the pore wall are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 116 publications
0
7
1
Order By: Relevance
“…Still, comparing the fitted time constants τ 1 = 200 s and τ 2 = 9000 s to τ n = 2.9 × 10 2 s and τ ad = 4.8 × 10 2 s as stated in the main text, respectively, we see that our model predicts both timescales within approximately one order of magnitude. Even though we seem to predict τ 1 better than τ 2 , using a smaller diffusion constant D = 2 × 10 −10 m 2 s −1 , to account for slow diffusion in pores [31,39], leads to τ n = 2.3 × 10 3 s and τ ad = 3.6 × 10 3 s and predictions for τ 2 are better than for τ 1 .…”
Section: Appendix C: Comparison To Experimental Surface Charge Build Upcontrasting
confidence: 55%
See 1 more Smart Citation
“…Still, comparing the fitted time constants τ 1 = 200 s and τ 2 = 9000 s to τ n = 2.9 × 10 2 s and τ ad = 4.8 × 10 2 s as stated in the main text, respectively, we see that our model predicts both timescales within approximately one order of magnitude. Even though we seem to predict τ 1 better than τ 2 , using a smaller diffusion constant D = 2 × 10 −10 m 2 s −1 , to account for slow diffusion in pores [31,39], leads to τ n = 2.3 × 10 3 s and τ ad = 3.6 × 10 3 s and predictions for τ 2 are better than for τ 1 .…”
Section: Appendix C: Comparison To Experimental Surface Charge Build Upcontrasting
confidence: 55%
“…The electrodes were immersed in a 1 M NaCl solution at room temperature, hence, κ −1 = 0.3 nm and bulk diffusivity D = 1.6 × 10 −9 m 2 s −1 . [We ignore that D is smaller in nanopores [31,39] and that different diffusivities may appear in Eqs. ( 4) and ( 5) [42].]…”
mentioning
confidence: 99%
“…Although united atom MD simulations cannot access the length and temporal scales of coarse-grained DPD simulations, they are still capable of modeling larger systems without compromising much of the detailed atomic-level information. Allahyarov et al applied united-atom MD simulations to investigate the effects of the lengths of the backbone segment and side chain in different confinements on the hydrophilic cluster morphology and proton transport in Nafion-type ionomers. The authors modeled the variations of Nafion under low hydration levels in which the lengths of the backbone segments and side chains are up to 2- and 3-fold higher than in original Nafion, respectively .…”
Section: Proton Exchange Membranesmentioning
confidence: 99%
“…The longer side chains facilitate the formation of larger clusters with higher sulfonate density, which to some extent improves proton transport . Another study investigated the morphological changes induced by a cylindrical pore confinement in Nafion-type ionomers. , They found that the pore diameter and sulfonate density play an important role in ionic cluster shape and transport properties. Specifically, a branched wire-like network was observed along with the pore axis in the larger pores, while sulfonate head groups tend to form smooth clusters in the center part of the pores as the pore diameter is decreased.…”
Section: Proton Exchange Membranesmentioning
confidence: 99%
See 1 more Smart Citation